Screening of Pre-Diabetes and Type-II Diabetes Mellitus Among the Personnel of Bangladesh Air Force - Al Mamun, A K M; Mohsin, Mohammad; Jesmine, Rezina; Ali, Md Sihab (Bangladesh Armed Forces Medical Journal, 2024)
Background: Medical Squadron (Med Sqn) of Bangladesh Air Force (BAF) Base Bashar (BSR) has been providing medical support for BAF Base BSR, Air Headquarters, most of the retired officers and their families. It has been observed that the number of Diabetes Mellitus (DM) patient is increasing day by day, and now it becomes a major health problem among the members of BAF, even among the young age group. In view of above, a study was conducted among the BAF uniform members who reported for laboratory investigation to Med Sqn BAF Base BSR. Assessing prevalence of DM among BAF personnel will also help for overall assessment of health problem of BAF personnel to make a preventive guideline. Methods: A descriptive type of cross-sectional study was conducted with available data in the pathological laboratory of Med Sqn BAF Base BSR during the period from 01 July 2021 to 30 Jun 2022. Within this period a total 9269 Air Force uniform members reported for routine as well as diagnostic purpose of checking blood sugar. Associated risk factor like overweight or obesity was also assessed by latest data from personal documents. Age and job pattern wise data were also analyzed. Statistical Package for Social Sciences (SPSS) version 29.0 was used to analyze data. Results: Out of 9269 BAF members a total 683 persons (7.36%) had high (above normal) plasma glucose. Of these 413(60.46%) were diabetic and 270(39.53%) were pre-diabetic (IFG/IGT). Among the 413 diabetic patients 292(42.75%) had fasting plasma glucose (FPG) ≥7 mmol/L as well as post prandial plasma glucose (PPPG) level ≥11.1 mmol/L. Among the 270 pre-diabetic patients 205(30.01%) had FPG level between 6.1-6.9 mmol/L with PPPG level <7.8 mmol/L (Impaired Fasting Glucose/IFG) and 65(9.51%) had FPG level <7 mmol/L with PPPG level between 7.8-11 mmol/L (Impaired Glucose Tolerance/IGT). Conclusion: DM has become a major health concern all over the world. This study attempted to identify the prevalence of age-related factors for DM among BAF uniform members between the ages 30 to 60 years. It has been observed that the prevalence of pre-diabetes is more among the 41 to 45 years age group and Type-II DM among the 46-50 years age group. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 22-27